2020
DOI: 10.1002/acn3.51231
|View full text |Cite
|
Sign up to set email alerts
|

Corpus callosum integrity loss predicts cognitive impairment in Leukoaraiosis

Abstract: Objective: To investigate regional white matter fibers loss in Leukoaraiosis (LA) and its relationship with cognitive impairments. Methods: Fifty-six participants with LA and 38 healthy controls underwent clinical evaluations and MR scans. Participants with LA were classified as cognitively normal (LA-NC, n = 18), vascular cognitive impairment of none dementia (LA-VCIND, n = 24), and vascular dementia (LA-VaD, n = 14) by Mini-Mental State Examination and Clinical Dementia Rating. Cognitive domains including vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
(126 reference statements)
1
7
0
Order By: Relevance
“…Consistent with previous studies (Lin et al, 2015 ; Tu et al, 2017 ; Chen et al, 2018 ; Liu et al, 2019 ; Wang et al, 2020 ), the strongest associations between abnormal DTI parameters and cognitive decline were found in the CC and corona radiata. As one of the most extensively myelinated brain regions, the CC is composed of fibers arising from large pyramidal neurons, with the anterior portion containing axons of corticocortical communicating fibers from corresponding posterior lobar regions (Matsunami et al, 1994 ; Abe et al, 2004 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous studies (Lin et al, 2015 ; Tu et al, 2017 ; Chen et al, 2018 ; Liu et al, 2019 ; Wang et al, 2020 ), the strongest associations between abnormal DTI parameters and cognitive decline were found in the CC and corona radiata. As one of the most extensively myelinated brain regions, the CC is composed of fibers arising from large pyramidal neurons, with the anterior portion containing axons of corticocortical communicating fibers from corresponding posterior lobar regions (Matsunami et al, 1994 ; Abe et al, 2004 ).…”
Section: Discussionsupporting
confidence: 90%
“…Loss of WM tract integrity in SVCI has been observed by neuroimaging. For example, microstructural damage in the anterior corpus callosum (CC), internal and external capsules, and periventricular WM has been demonstrated in SVCI by tract-based spatial statistics (TBSS; Papma et al, 2014 ; Holland et al, 2015 ; Chen et al, 2018 ; Wang et al, 2020 ), which also revealed significant associations between microstructural changes in WM tracts underlying intra-and inter-hemispheric cerebral, thalamocortical, and cerebello-thalamic connections—including the CC and corona radiata—and cognitive performance (van der Holst et al, 2018 ; Mascalchi et al, 2019 ). An automated fiber quantification (AFQ) study found that changes in diffusion characteristics—especially in the right inferior fronto-occipital fasciculus and right inferior longitudinal fasciculus—may be involved in WMH-related MCI (Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] More importantly, loss of corpus callosum integrity has been shown to be associated with cognitive decline, especially impaired executive processing, in subjects with WMI. [ 21 ] The BCAS rodent model is commonly used to mimic cognitive deficits in humans caused by cerebral hypoperfusion due to vascular diseases. [ 16 ] In this study, we found that the extent of working memory impairment was positively correlated with that of myelin loss in the corpus callosum, indicating that slowing or reversing WMI might be a promising therapeutic strategy for WMI‐related cognitive deficits.…”
Section: Discussionmentioning
confidence: 99%
“…The thalamus plays a vital role in various cognitive processes, including attention, executive ability, and working memory. The head of the caudate nucleus is an essential component of the cognitive circuit because it links the frontal lobe, the thalamus, the limbic system, and other structures; it also receives signals from frontal and temporoparietal regions bilaterally and sends out efferent fibers to the different areas of the basal ganglia ( 40 ). We considered that acute cerebral infarction caused the aforementioned microstructural disruption in 8 brain regions intimately connected to cognitive function.…”
Section: Discussionmentioning
confidence: 99%